Dual-Pathway Inhibition with Rivaroxaban and Low-Dose Aspirin Does Not Alter Immune Cell Responsiveness and Distribution in Patients with Coronary Artery Disease - Laszlo A. Groh; Loes H. Willems; Paula Fintelman; Michel M. P. J. Reijnen; Saloua El Messaoudi; Michiel C. Warlé (Cardiology and Therapy, 2023)
Abstract Introduction Cardiovascular diseases (CVD) are the leading cause of death globally. Inflammation is an important driver of CVD where tissue damage may lead to the formation of deadly thrombi. Therefore, antithrombotic drugs, such as platelet inhibitors, are crucial for secondary risk prevention in coronary artery disease (CAD) and peripheral artery disease (PAD). For severe forms of the disease, dual-pathway inhibition (DPI) where low-dose aspirin is combined with rivaroxaban has shown improved efficacy in reducing cardiovascular mortality. Methods Given this greater improvement in mortality, and the importance of inflammation in driving atherosclerosis, the potential for off-target inflammation-lowering effects of these drugs was evaluated by looking at the change in immune cell distribution and responsiveness to ex vivo lipopolysaccharide (LPS) stimulation after 3 months of DPI in patients with CAD. Results We observed no changes in whole blood or peripheral blood mononuclear cell (PBMC) immune cell responsiveness to LPS after 3 months of DPI. Additionally, we did not observe any changes in the distribution of total white blood cells, monocytes, neutrophils, lymphocytes, or platelets during the study course. Signs of systemic inflammation were studied using Olink proteomics in 33 patients with PAD after 3 months of DPI. No changes were observed in any of the inflammatory proteins measured after the treatment period, suggesting that the state of chronic inflammation was not altered in these subjects. Conclusion Three months of DPI does not result in any meaningful change in immune cell responsiveness and distribution in patients with CAD or PAD. Trial Registration ClinicalTrials.gov ID: NCT05210725